The Influence of Perceptions, Motivation, Interests, and Knowledge of Students about Tax on Career Choices in Taxation: (Empirical Studies on Accounting Students Class of 2019 and 2020, Narotama University, Surabaya) - Adinda Oktavia; Ibnu Fajarudin (NAROTAMA UNIVERSITY, Indonesia, 2023)
The purpose of this study was to determine the effect of student perceptions, student career motivation, student job market consideration motivation, student interest, and student knowledge about taxes on career choices in taxation. This research was conducted at Narotama University in Surabaya, especially the Accounting study program in the choice of a career in the field of taxation. The sample in this study used a purposive sampling technique including accounting students in 2019 and 2020 with a total population of 110 students with a sampling technique using the slovin formula. The research instrument used a questionnaire which was then tested with the help of the SPSS version 26 application. From the test, it was found that the student perception variable partially has no effect on career choices in the field of taxation. The variable of student career motivation partially has a significant effect on career choices in the field of taxation. Variable motivation in consideration of the student labor market partially has no effect on career choices in the field of taxation. The student interest variable partially has a significant effect on career choices in the field of taxation. The variable of student knowledge about taxes partially has a significant effect on career choices in the field of taxation. Simultaneously student perceptions, student career motivation, student job market consideration motivation, student interests, and student knowledge about taxes influence career choices in the field of taxation.